1971
DOI: 10.1039/c29710000266
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-induced shifts in nuclear magnetic resonance spectroscopy: application to ketones

Abstract: The shifts induced by tris(dipiva1omethanato)praseodymium, Pr(dpm),, in the n.m.r. spectra of 4-t-butylcyclohexanone and 2,2-dimethyl-4-t-butylcyclohexanone vary linearly with concentration of Pr(dpm) and are ca. 1-4 times as large as those obtained with =u(dPm) 3' THE REPORTS of Hinckleyl and of Sanders and Williams2 on the paramagnetic shifts induced in organic compounds using tris(dipivalomethanato)europium(m) , Eu(dpm) 3, have led to studies by other worker~.~-S The majority of the structures so far examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The inversion of NMR spectra with upfield shift reagents can contradict our sense of NMR spectra. In some cases, praseodymium(III) complexes have been applied to move the resonances of methyl groups to still higher fields (Belanger et al, 1971a(Belanger et al, , 1971b.…”
Section: Achiral Shift Reagentsmentioning
confidence: 99%
“…The inversion of NMR spectra with upfield shift reagents can contradict our sense of NMR spectra. In some cases, praseodymium(III) complexes have been applied to move the resonances of methyl groups to still higher fields (Belanger et al, 1971a(Belanger et al, , 1971b.…”
Section: Achiral Shift Reagentsmentioning
confidence: 99%
“…For steric reasons, coordination to LSR involves the intracyclic and not the more basic exocyclic oxygen atom in 57 and 58.276'293'294 '399 For example, in 58 the induced shifts decrease in the order Ha = Hb > Hc > Hd > OCH2Me, thus establishing the stereochemistry of the saturated ring and showing the lower donor properties of the exocyclic ether. By contrast, Scharf has found that 59 forms a chelate with Eu(thd>3 via the vicinal cis pair of methoxy groups.295 In a bisphenol diglycidyl ether, complexing involves the epoxy rather than the exo ethereal oxygen.408 Ethers are invariably stronger donors than thioethers,72•97'232 e.g., 60, in which approximately 70% of the LSR is coordinated to the oxygen, and 61,97 Surprisingly the sulfone group is a weaker donor than an ether,296 and in the thiophene derivative 62 complexing is confined to the oxygen, enabling assignment of two isolated isomers to two out of the four possible stereoisomers.83 Of several reports concerning epoxides, three are complicated as they concern compounds which contained five to seven other heteroatoms.103•114•279 Manni's study of the LIS of diepoxybutanes and diepoxyoctanes and the epoxide-lactone 63 is more helpful.124 The largest LIS is observed for the protons cis to the epoxide ring, but comparison with LIS of the model compound cyclohexene oxide shows that competing coordination is occurring with the lactone. However, clearly epoxidation provides an efficient means of gaining spectral simplification of alkenes.…”
Section: Ethers and Epoxidesmentioning
confidence: 99%
“…(i) Only strong Lewis bases exhibit useful induced shifts with metal chelates, small or negligible shifts being observed for ketones, ethers, and sulfoxides. 60 (ii) Contact shift interactions may make a very sizable contribution to the observed anisotropic shifts (cf. section II.B).5…”
Section: Paramagnetic Salts and Chelates Of Transition Metalsmentioning
confidence: 99%
“…Several comparisons of Eu(DPM)3 and Pr(DPM)3 as shift reagents have been reported (2,3,5,38). While the praseodymium reagent induces larger shifts than does the europium complex in similar concentrations, the former suffers a greater loss of resolution.…”
mentioning
confidence: 99%